Dipterocarpus tuberculatus as a promising anti-obesity treatment in Lep knockout mice - Roh, Yu Jeong; Lee, Su Jin; Kim, Ji Eun; Jin, You Jeong; Seol, Ayun; Song, Hee Jin; Park, Jumin; Park, So Hae; Douangdeuane, Bounleuane; Souliya, Onevilay; Choi, Sun Il; Hwang, Dae Youn (Frontiers in Endocrinology, 2023)
Introduction: The therapeutic effects and mechanisms of Dipterocarpus tuberculatus (D. tuberculatus) extracts have been examined concerning inflammation, photoaging, and gastritis; however, their effect on obesity is still being investigated. Methods: We administered a methanol extract of D. tuberculatus (MED) orally to Lep knockout (KO) mice for 4 weeks to investigate the therapeutic effects on obesity, weight gain, fat accumulation, lipid metabolism, inflammatory response, and β-oxidation. Results: In Lep KO mice, MED significantly reduced weight gains, food intake, and total cholesterol and glyceride levels. Similar reductions in fat weights and adipocyte sizes were also observed. Furthermore, MED treatment reduced liver weight, lipid droplet numbers, the expressions of adipogenesis and lipogenesis-related genes, and the expressions of lipolysis regulators in liver tissues. Moreover, the iNOS-mediated COX-2 induction pathway, the inflammasome pathway, and inflammatory cytokine levels were reduced, but β-oxidation was increased, in the livers of MED-treated Lep KO mice. Conclusion: The results of this study suggest that MED ameliorates obesity and has considerable potential as an anti-obesity treatment.